Seismic forward modelling constraints for seismic ore exploration at the Kylylahti Cu-Co-Zn-Ni-Ag-Au sulfide deposit - Tuomi, Hilkka (Helsingfors universitet, 2016)
The Kylylahti Cu-Co-Zn-Ni-Ag-Au sulfide deposit is located within the Paleoproterozoic North Karelia Schist Belt in eastern Finland about 25 km northeast from Outokumpu. The Kylylahti deposit is a part of the deformed and discontinuous chain of occurrences of Outokumpu assemblage in the Outokumpu area. Outokumpu assemblage refers to a lens-shaped serpentinized peridotite body enveloped by carbonate-skarn-quartz rocks. In the entire Outokumpu area the Cu-Co-Zn-Ni-Ag-Au massive to semi-massive sulfide deposits are hosted in the thin carbonate-silica alteration zones around the serpentinite bodies and are surrounded by black schists. The Kylylahti serpentinites are fine-grained and massive antigorite serpentinites. Tremolite skarns are abundant within the alteration zones of the Kylylahti massif. Previous seismic reflection data from the Outokumpu area includes OKU1, OKU2 and OKU3 survey lines acquired in connection with the Finnish Reflection Experiment FIRE in 2001–2005 and V1, V2, V3, V7, V8 and E1 survey lines in connection with the High Resolution Reflection Seismics for Ore Exploration HIRE in 2007–2010. The goals of this work were, 1) to estimate the seismic reflectivity characteristics of the Outokumpu-type ores and various rock types in the Outokumpu area, 2) to build a geological 3D model of the Kylylahti massif, 3) to use this 3D model and the estimated seismic velocity and density values for creating synthetic seismic sections over the Kylylahti massif in order to test for optimal 2D reflection seismic survey geometries and 4) to compare the synthetic sections with real reflection seismic sections already available from the Kylylahti area. For seismic forward modelling, a geological 3D model and densities and seismic velocities of different rock types are needed. Density values for each rock type were chosen from and compared with previous density measurements done in the entire Outokumpu area. Several rock types show a trend of increasing density towards Kylylahti. Seismic velocity values were either ...